Implementasi Kebijakan Perizinan Pelayanan Terpadu Satu Pintu pada Kantor Wilayah Kementerian Agama Provinsi Gorontalo - Pratia Anggraini Wahap; Sri Yulianty Mozin; Yakop Noho Nani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study aims to examine and analyze the process of implementing the one-stop integrated service licensing policy at the Regional Office of the Ministry of Religious Affairs of Gorontalo Province, focusing on organization, interpretation, and application. A qualitative approach with a descriptive method was employed. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, with data validation via triangulation. The results indicate that implementing the One- Stop Integrated Service Licensing at the Regional Office of the Ministry of Religious Affairs of Gorontalo Province has not been optimally executed following Ministerial Regulation (PMA) Number 65 of 2016. Several aspects evidence this: Organization has not fully optimized resources and lacks facilities such as filing cabinets and computers; Interpretation has been limited, as the socialization provided only covers schedules and service structures, leaving PTSP managers without a clear understanding of the technical rules and services; Application remains ineffective and inefficient, with services not well-integrated, resulting in administrative processes being centralized in specific fields. The study recommends that the PTSP at the Regional Office of the Ministry of Religious Affairs of Gorontalo Province adhere consistently to PMA Number 65 of 2016 regarding Integrated Services, optimize human resources both quantitatively and qualitatively, and improve facilities and infrastructure.